COVID-19 AND FUTURE TRAVEL DECISIONS: HOW DO THE DESTINATION-CHOICE-BASED MOTIVATORS REDEFINE TOURIST’S CHOICES? - Bipithalal Balakrishnan Nair; Satyajit Sinha (Enlightening Tourism: A Pathmaking Journal)
COVID-19 has heavily influenced people all around the world and forced us to acclimatise to a New Normal. Post-COVID-19 scenarios are predicted that impose specific criteria on travel choices that could change the present tourism equilibrium. Addressing these impulses is crucial for travel destinations for their resilience and recovery. This paper presents preliminary insights into present travel decisions and speculates about potential future, post-COVID-19 choices. An online survey of 449 participants used to investigate the underlying dimensions of destination selection motivations, and to explore the significant differences between the characteristics of travellers in destination-choice-based motivators (DCBMs) for destination selections post-COVID-19. Three motivators for the choice of destinations were derived: accessibility and discounting, health and hygiene, and the history of low incidences of COVID-19. Results also identified interrelationships between travel history and destination selection motivators: participants who had undergone a prolonged quarantine period were highly motivated by ‘accessibility and discounting’ and ‘health and hygiene’ factors. In contrast, people with no international travel experience were more concerned with low COVID-19 incidences in the destination(s).